Confining donor conformation distributions for efficient thermally activated delayed fluorescence with fast spin-flipping - Qiu, Weidong; Liu, Denghui; Li, Mengke; Cai, Xinyi; Chen, Zijian; He, Yanmei; Liang, Baoyan; Peng, Xiaomei; Qiao, Zhenyang; Chen, Jiting; Li, Wei; Pu, Junrong; et al. (Nature communications, 2023)
Fast spin-flipping is the key to exploit the triplet excitons in thermally activated delayed fluorescence based organic light-emitting diodes toward high efficiency, low efficiency roll-off and long operating lifetime. In common donor-acceptor type thermally activated delayed fluorescence molecules, the distribution of dihedral angles in the film state would have significant influence on the photo-physical properties, which are usually neglected by researches. Herein, we find that the excited state lifetimes of thermally activated delayed fluorescence emitters are subjected to conformation distributions in the host-guest system. Acridine-type flexible donors have a broad conformation distribution or bimodal distribution, in which some conformers feature large singlet-triplet energy gap, leading to long excited state lifetime. Utilization of rigid donors with steric hindrance can restrict the conformation distributions in the film to achieve degenerate singlet and triplet states, which is beneficial to efficient reverse intersystem crossing. Based on this principle, three prototype thermally activated delayed fluorescence emitters with confined conformation distributions are developed, achieving high reverse intersystem crossing rate constants greater than 10 6 s −1 , which enable highly efficient solution-processed organic light-emitting diodes with suppressed efficiency roll-off. The distribution of dihedral angles in film state has significant influence on excited state lifetimes of thermally activated delayed fluorescence emitters. Here authors report conformation distribution confinement strategy to achieve fast spin-flipping for efficient organic light-emitting diodes.